1998
DOI: 10.1046/j.1365-2435.1998.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological health state indices of reproducing Great Tits: a response to brood size manipulation

Abstract: Summary 1.A brood size manipulation experiment was performed in two Great Tit (Parus major L.) populations in order to evaluate the effect of raising different numbers of nestlings on parental health state. 2. Brood enlargement resulted in elevated heterophile:lymphocyte ratios and decreased lymphocyte number in the peripheral blood, indicating that increased reproductive effort causes immunosuppression. 3. Haematocrit increased in response to brood enlargement, suggesting a response to the requirement of elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 27 publications
(33 reference statements)
8
95
0
1
Order By: Relevance
“…For example, haematocrit was not influenced by the presence of Haemoproteus parasites in great tits but increased in response to brood enlargement [57]. This last result was interpreted as the response to the requirement of elevated oxygen-carrying capacity owing to increased work load [57]. The negative relationship between parasitaemia and haematocrit in the present study suggests that Plasmodium parasites are more virulent than Haemoproteus and destroy a larger amount of erythrocytes (98% of Plasmodium sp.…”
Section: (C) Prevalence and Parasitaemiasupporting
confidence: 42%
See 1 more Smart Citation
“…For example, haematocrit was not influenced by the presence of Haemoproteus parasites in great tits but increased in response to brood enlargement [57]. This last result was interpreted as the response to the requirement of elevated oxygen-carrying capacity owing to increased work load [57]. The negative relationship between parasitaemia and haematocrit in the present study suggests that Plasmodium parasites are more virulent than Haemoproteus and destroy a larger amount of erythrocytes (98% of Plasmodium sp.…”
Section: (C) Prevalence and Parasitaemiasupporting
confidence: 42%
“…An increase in heterophil : lymphocyte ratio, a signal of stress, among birds making an intense parental effort further suggests a trade-off between reproductive effort and health state in great tits [57,59]. A study carried out by Horák et al [57] in great tits tried to evaluate the effects of reproductive effort on health status by brood manipulation. The authors observed that the number of lymphocytes in the peripheral blood decreased with the increase of parental effort and suggested that reproductive effort could lead to suppression of the immune response.…”
Section: (C) Prevalence and Parasitaemiamentioning
confidence: 99%
“…This probably occurs because there is an increase in energy demand during the reproductive period (oviposition, incubation and parental care energy costs) and consequently an increase of oxygen consumption and the need for hemoglobin and CHGM to transport it. OTS & HÕRAK (1996), HÕRAK et al (1998) and KILGAS et al (2006) also noticed that in the breeding season the extra efforts result in an health aggravation.…”
Section: Discussionmentioning
confidence: 99%
“…Small increases in CORT are likely to drive these individuals to forage more and expend more energy, and this could explain their relatively high haematocrit concentrations (mean > 60). High haematocrit concentrations in birds are often attributed to extreme dehydration or increases in energy demands, such as cold stress and increased activity during breeding or migration (Carpenter 1975;Breuer et al 1995;Horak et al 1998;Box et al 2002;Fair et al 2007). However, all finch species showed no significant seasonal differences in haematocrit, and without obvious changes in haematocrit above or below mean concentrations, interpretation of the reason for relatively high haematocrit values is not possible (Fair et al 2007).…”
Section: Correlations Between Stress and Condition Indicesmentioning
confidence: 99%